2016
DOI: 10.21608/jppp.2016.52431
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Two Fixed Plant Oils by Using a New Fumigant Method Against Trogoderma granarium Everts and Stegopium paniceum (L.)

Abstract: The present research was achieved to study the toxicity of fixed oils of clove buds (Syzygium aromaticum) and spearmint leaves(Mentha spicata) against larvae and adults of Khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae) and the adults of the drugstore beetle, Stegobium paniceum (L.) by using a new fumigant technique. Germination test was conducted in order to assess the effect of tested oils at the highest concentration on wheat seeds after 24 hrs. A GC/MS analysis was performed to record … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The high repellent activity of S. aromaticum EO may be due to eugenol because it is the main constituent of clove oil (48.92%) as determined by GC-MS [ 31 ]. Moreover, Boraei [ 32 ] reported that the main component of clove EO was eugenol (37.43%). In many previous studies, this component has been indicated to be a strong repellent compound against many insect pests [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high repellent activity of S. aromaticum EO may be due to eugenol because it is the main constituent of clove oil (48.92%) as determined by GC-MS [ 31 ]. Moreover, Boraei [ 32 ] reported that the main component of clove EO was eugenol (37.43%). In many previous studies, this component has been indicated to be a strong repellent compound against many insect pests [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%